Design and development of a smart picosatellite - Tay, Willie Shao Liang (2014)
Miniaturised satellites have been gaining popularity and widely explored due to its huge cost saving potential, and its ability to customise payloads for specific missions. Using of Commercial Off-The-Shelf (COTS) products in miniaturised satellites not only further pushes down the cost of production and launch, but also helps in saving time and allows easier implementation for its systems.